ANALISIS KEBIJAKAN PEMERINTAH DAERAH SUMEDANG DALAM PENGEMBANGAN DESA WISATA RANCAKALONG - Taufik Fikrya Suminta; Gilang Pratama Putra; Irena Novarlia (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2026)
This study aims to analyze the local government's policies in Sumedang Regency regarding the development of tourism in Rancakalong Village, as well as to identify the factors supporting and hindering the implementation of these policies. Rancakalong Village possesses significant tourism potential, yet it has not been fully developed and utilized optimally. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that the local government's policies for tourism development in Rancakalong Village include efforts to improve infrastructure, promote tourism, and empower the local community. However, the implementation of these policies faces several challenges, such as budget constraints, lack of coordination among agencies, and minimal active participation from the community. On the other hand, strong local government support and the presence of unique natural and cultural tourism potential are the main factors supporting tourism development in this village. The conclusion of this study is that although the implemented policies are on the right track, there is a need for enhanced coordination, more adequate budget allocation, and more intensive community involvement to ensure that tourism development in Rancakalong Village can proceed more effectively and sustainably. The recommendations include increasing synergy between the government, the community, and the private sector in tourism development, as well as enhancing the capacity of local human resources.